Hunger climate vulnerability index (HCVI) and macroeconomic indicators downstream of Bengawan Solo Watershed. Issue 1 (July 2021) - Suryanto,; Utomowati, R; Gravitiani, E; Rosalia, A C T
Abstract: This studi aims to investigate: 1) the level of Hunger Climate Vulnerability Index (HCVI)) among the regencies, 2) correlation between macroeconomic indicator and Hunger Climate indicators such as economic growth and poverty, and 3) mapping of comparison of HCVI in Watershed of Bengawan Solo covering Bojonegoro, Tuban, Lamongan and Gresik. Topographically, downstream of Bengawan Solo Watershed is the area most prone to flooding. If the threat of climate change becomes more apparent where potential shifts and rainfall intensity will increase the risk of flooding especially in the agricultural sector. The method used in this research by using the score of HCVI, correlation analysis, and geographic information system (GIS). The HCVI represents the level of people's vulnerability as the impact of disasters (i.e., floods) attacked their region. The third tool is - GIS; this tool is used to mapping the result of the HCVI and correlation among the HCVI, economic growth, and poverty index. The results showed the highest score of the HCVI score respectively obtained by Tuban Districts Bojonegoro, Lamongan, and Gresik. For the grade of HCVI, Tuban Districts and Bojonegoro Districts are categorized into high, Lamongan Districts are moderate, and Gresik Districts are the lowest. Indicators of macroeconomics, such as poverty index supported the HCVI score. Meanwhile the macro-economic indicators especially economic growth do not represent the HCVI score.